Removing of Cadmium Ions and Reactive red Dye from Simulated Wastewater Using Eggshell as an Eco-Friendly Material - Yousra Mohamed; Waleed M. Abood; Faten Hameed Kamil; Zuhair Khedair (Iraqi Journal of Industrial Research)
The research aims to use eggshells (ES) as civilian residues in the process of removing cadmium ions and reactive red dye according to international standards limits. Synthetic solutions were prepared for cadmium ions and reactive red dye using 0.2 g non-calcined and calcined ES at various temperatures (25, 250, 500, 750, and 1000 ℃) as an adsorbent.  The result showed the removal of cadmium ion was (60, 100%) for non-calcined and calcined ES, respectively, with the initial concentration of cd2+ (10 ppm). The removal of reactive red dye was (18.5, 98%) using non-calcined and calcined ES, respectively, at a concentration of red dye (50 ppm). The best removal time was 90 min.  XRD and FTIR spectroscopy were performed and the results were identical to the main components of ES and changed with temperature increasing due to dissolution of calcium carbonate (CaCO3).